Introducing Waqf Based Takaful Model in India - Syed Ahmed Salman; Sheila Nu Nu Htay (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective – Waqf is a unique feature of the socioeconomic system of Islam in a multi- religious and developing country like India. India is a rich country with waqf assets. The history of waqf in India can be traced back to 800 years ago. Most of the researchers, suggest how waqf can be used a tool to mitigate the poverty of Muslims. India has the third highest Muslim population after Indonesia and Pakistan. However, the majority of Muslims belong to the low income group and they are in need of help. It is believed that waqf can be utilized for the betterment of Indian Muslim community. Among the available uses of waqf assets, the main objective of this paper is to introduce waqf based takaful model in India. In addition, how this proposed model can be adopted in India is highlighted.Methods – Library research is applied since this paper relies on secondary data by thoroughlyreviewing the most relevant literature.Result – India as a rich country with waqf assets should fully utilize the resources to help the Muslims through takaful.Conclusion – In this study, we have proposed waqf based takaful model with the combination of the concepts mudarabah and wakalah for India. We recommend this model based on the background of the country and situations. Since we have not tested the viability of this model in India, future research should be continued on this testing.Keywords : Wakaf, Takaful, Kemiskinan dan India